Groundstroke Training Equipment Innovation for Beginner Tennis Players - Lazuardy Akbar Fauzan; Muhammad Mulhim; Edwin Wahyu Dirgantoro; Akhmad Amirudin; Perdinanto Perdinanto (Indonesian Journal of Physical Education and Sport Science)
Study Purpose. Forehand and backhand groundstrokes are the basic strokes in tennis that need to be mastered. The training process needs to be supported by the availability of training equipment facilities so that it can help athletes and coaches to achieve training goals. The aim of this research is to produce an innovative tennis groundstroke training tool for beginner players. The novelty in this research is that it produces an innovative tennis groundstroke training tool that can be used for forehand and backhand training.